1999
DOI: 10.1144/gsjgs.156.3.0633
|View full text |Cite
|
Sign up to set email alerts
|

Structural evolution of shale diapirs from reactive rise to mud volcanism: 3D seismic data from the Baram delta, offshore Brunei Darussalam

Abstract: Two areas of shale diapirism in a deltaic setting were examined using 3D seismic data from offshore Brunei to determine the origin, evolution and geometry of shale diapirs. The study areas cover parts of the Egret and Ampa fields within the Baram Delta province. The Ampa diapir consists of a small bulge of the mobile Setap shale around which lies a zone of chaotically disrupted country-rock reflections. At the crest of this chaotic zone, vertical, cylindrical shale pipes arise that end in a wider head. The dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(92 citation statements)
references
References 20 publications
3
87
0
2
Order By: Relevance
“…Resurgence of activity correlates with local earthquakes. Recently, two geophysical studies have shown MVism onshore [Morley et al, 1998] and offshore of Brunei [Van Rensbergen et al, 1999]. Regarding the first, multiphase intrusion of shale, indicated from dyke formation patterns, affected mid-Miocene anticlinal sediments [Morley et al, 1998].…”
Section: A33 Brunei/borneo and Sabahmentioning
confidence: 99%
See 2 more Smart Citations
“…Resurgence of activity correlates with local earthquakes. Recently, two geophysical studies have shown MVism onshore [Morley et al, 1998] and offshore of Brunei [Van Rensbergen et al, 1999]. Regarding the first, multiphase intrusion of shale, indicated from dyke formation patterns, affected mid-Miocene anticlinal sediments [Morley et al, 1998].…”
Section: A33 Brunei/borneo and Sabahmentioning
confidence: 99%
“…More recently, subsequent erosion and uplift remobilized the shale bodies and gave way to MV formation in the Jerudong anticline [Morley et al, 1998]. In the Ampa and Egret areas offshore in the Baram delta, the situation is more complex, with an intrusive phase followed by MVism, which in turn got buried, before migrating gas and water may have helped a renewal of ascent and extrusion [Van Rensbergen et al, 1999]. High-resolution seismic data across the structures suggest an interfingering of shales (showing a chaotic texture with incorporated country rock) and the wall rock (well stratified sediment).…”
Section: A33 Brunei/borneo and Sabahmentioning
confidence: 99%
See 1 more Smart Citation
“…The model proposed by Brown (1990), Van Rensbergen et al (1999), Davies and Stewart (2005), and Stewart and Davies (2006) is that hydrofractures can penetrate several kilometers of the crust and transport a fluid-sediment mix that erupts to form a pioneer volcano. Because in this case we know that the mud-water mix has been transported ~2 km through the overburden, through new or reactivated fractures, the Lusi eruption supports the models proposed by these authors.…”
Section: Initiation and Subterranean Mixingmentioning
confidence: 99%
“…Luo et al (1994) conclude that most of the pore-fluid generating mechanisms (illite to smectite transforma tion, aquathermal expansion, kerogen maturation) contribute little to overpressure increase. Kerogen to gas or oil to gas transition produce significant volume changes (Rensbergen et al, 1999). In addition, Forbes et al (1992) and Sandal (1996) report that even thin units of a rock can form effective permeability barriers.…”
Section: Chapter IV Discussion and Conclusionmentioning
confidence: 99%